Bevacizumab in ovarian cancer: Focus on clinical data and future perspectives. (January 2016) - Colombo, Nicoletta; Conte, Pier Franco; Pignata, Sandro; Raspagliesi, Francesco; Scambia, Giovanni
Abstract: The past five years have yielded substantial developments in the management of advanced ovarian cancer. Initial promise shown by anti-angiogenic agents has translated into positive phase III trials in the front-line and recurrent settings. Nevertheless, several questions remain unanswered, including the most appropriate timing for initiation of anti-angiogenic therapy and patient selection for the various treatment approaches. This review article summarises the key results (including final overall survival data), from five pivotal phase III trials of bevacizumab, highlights emerging data with new maintenance strategies and considers unanswered questions and ongoing research to address uncertainties in treatment duration, re-exposure to bevacizumab in bevacizumab-pretreated patients and the potential integration of anti-angiogenic therapy into neoadjuvant treatment regimens.